Urbanisasi sebagai Pendorong Inovasi di Sektor Ekonomi Digital - Adine Ardiyanti; Sulistiawati Sulistiawati (Jurnal Penelitian Ilmu Ekonomi dan Keuangan Syariah, 2024)
Urbanization is a significant social phenomenon in developing countries, including Indonesia, characterized by the movement of populations from rural areas to cities. This process not only alters demographic structures but also brings social, economic, and environmental impacts. Urbanization can be defined as the transformation of homogeneous areas into heterogeneous ones, influenced by various factors, including migration and infrastructure development. This article also explores the relationship between urbanization and digital economic growth, which plays a crucial role in fostering innovation and entrepreneurship. In the digital era, digital marketing has become an essential tool for entrepreneurs to reach broader markets and enhance competitiveness. Through historical and contextual analysis, this article highlights the evolution of urbanization in Indonesia, from the era of kingdoms to colonial influences, as well as the challenges and opportunities faced in managing contemporary urbanization. This research aims to provide insights into the importance of adaptive and sustainable strategies in addressing the dynamics of ongoing urbanization